Bodily Integrity, Embodiment, and the Regulation of Parental Choice. (28th November 2017) - Fox, Marie; Thomson, Michael
Abstract : In this article we develop a new model of bodily integrity that we designate 'embodied integrity'. We deploy it to argue that non‐therapeutic interventions on children should be considered within a decision‐making framework that prioritizes embodied integrity. This would counter the excessive decision‐making power that law currently accords to parents, protecting the child's immediate and future interests. Focusing on legal responses to genital cutting, we suggest that current legal understandings of bodily integrity are impoverished and problematic. By contrast, adoption of an 'embodied integrity' model carves out a space for children's rights, while avoiding these negative consequences. We propose that embodied integrity should trump competing values in any best‐interests assessment where a non‐therapeutic intervention is requested. Drawing on Drucilla Cornell and Joel Feinberg's theories we argue that protecting a child's embodied integrity is essential to guarantee his/her right to make future embodied choices and become a fully individuated person.